2009
DOI: 10.1177/039156030907604s01
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Tissue Resonance Interaction Method Probe (Trimprob Tm) in Non-Invasive Diagnosis of Prostatic Cancer. Analysis of the Results of 782 Patients

Abstract: The aim of our study was to evaluate the real utility of the TRIMprob test before TRUS-guided biopsy approach, putting in relation the number of positive tests of the TRIMprob with the number of positive prostate biopsies that were performed successfully. Sensitivity, Specificity, PPV (Positive predicted value), NPV (Negative predicted value) of the TRIMprob test were analyzed with statistical software package for Social Sciences (SPSS Inc, Chicago, Illinois USA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…These results have subsequently been replicated by other studies [68] and even by a multicenter trial [5], thus supporting also the reproducibility of the technique in detecting prostate cancer.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These results have subsequently been replicated by other studies [68] and even by a multicenter trial [5], thus supporting also the reproducibility of the technique in detecting prostate cancer.…”
Section: Discussionsupporting
confidence: 69%
“…Bellorofonte et al [ 4 ] were the first to evaluate the feasibility and diagnostic accuracy of TRIM-prob scanning in detecting prostate cancer; in their study population of 757 men, the test had a 95.5% sensitivity, a 42.7% specificity, a 63.6% PPV, and an 89.8% NPV. These results have subsequently been replicated by other studies [ 6 8 ] and even by a multicenter trial [ 5 ], thus supporting also the reproducibility of the technique in detecting prostate cancer.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The receiver of the TRIMprob detects the signal originating from non-linear resonance interactions of intensity expressed in arbitrary units ranging between 0 and 255. TRIMprob is a simple, quick to perform (in this study examination took less than 5 min) test that does not require any prior preparation of the patient, yielding immediate and reproducible results [ 5 , 6 , 11 ]. Previous clinical studies have shown that TRIMprob scanning is useful in detecting cancers of different localisations.…”
Section: Discussionmentioning
confidence: 99%
“…Using a wave frequency equal to half of the microtubule length was found to optimally detect cancerous growth. Several pilot clinical studies have shown that TRIMprob scanning is a valuable tool in diagnosing cancers developing in prostate [ 7 11 ], breast [ 12 ], stomach [ 13 ], thyroid gland [ 14 ], rectum [ 15 ], colon [ 16 ], or urinary bladder [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%